The Soviet City and its Everyday Life During the ‘Thaw’ Period in Oleg Khaneev’s Novella Life Lies Ahead of You, - Panasyuk, Valery (Literatūra, 2025)
The novella You Have Your Life Ahead of You by the journalist and prose writer Oleg Khaneev, published in Vilnius in 1962 by the State Publishing House of Fiction of the Lithuanian SSR, is analyzed within the conceptual framework of the hermeneutics of landscape. It should be noted that the novella represents an ideologically verified product, yet it is of interest for its depiction of Soviet everyday life. The article identifies the author’s distinctive portrayal of the city of Vilnius during the Soviet ‘Thaw’ era. It has been established that, according to its urban characteristics, the city in the novella represents a peripheral formation with its patriarchal everyday structure and corresponding behavioral patterns among its inhabitants. The dependence of Vilnius on the administrative centers of the Soviet Union is emphasized, as it is from these centers that symbolically and socially significant spiritual and material values are formulated and adopted.